Assessing the Consistency among Accounting Measures of Earnings Quality: A Study of Stocks Listed on National Stock Exchange 500 - Munjal, Shikhil; Singh, Gurcharan; Jearth, Palvi (International Journal of Economics and Financial Issues, 2021)
This paper examined the consistency among accounting measures of earnings quality for companies listed on National Stock Exchange 500 over the period 2008 to 2020. Earning is one of the most significant corporate financial information. Any investment choices are normally taken into account by taxpayers whenever making financial statements and benefit disclosures. Earnings measures actually allows investors to determine the financial results of the firms listed in the financial statements. The research employs four income quality accounting indicators, which are persistence, predictability, accrual quality, and smoothness. The spearman rank correlation is used to investigate consistency, which is a non-parametric test. The study showed that the indicators of earnings quality are not entirely consistent. For the sample period, majority of the times accrual quality and predictability is found to be significant. The results through spearman rank test implied that sample Indian firms have good accrual quality and predictability but lack of persistence and smoothness. Keywords: Earnings Quality, financial performance, spearman rank correlation, persistence, predictability, smoothness and accrual quality. JEL Classifications: M41, G32 DOI: https://doi.org/10.32479/ijefi.11405